Valorisation of the Invasive Macroalgae Undaria pinnatifida (Harvey) Suringar for the Green Synthesis of Gold and Silver Nanoparticles with Antimicrobial and Antioxidant Potential - Noelia González-Ballesteros; Mário Fernandes; Raúl Machado; Paula Sampaio; Andreia C. Gomes; Antonella Cavazza; Franca Bigi; Maria Carmen Rodríguez-Argüelles (Marine Drugs, 2023)
Bacterial and fungal infections are a challenging global problem due to the reported increasing resistance of pathogenic microorganisms to conventional antimicrobials. Nanomaterials are a promising strategy to fight infections caused by multidrug-resistant microbes. In this work, gold (Au@UP) and silver (Ag@UP) nanoparticles were produced for the first time by green synthesis using an aqueous extract of the invasive macroalgae Undaria pinnatifida (UP). The nanoparticles were characterized by a wide range of physicochemical techniques. Au@UP and Ag@UP demonstrated to be spherical and crystalline with an average size of 6.8 ± 1.0 nm and 14.1 ± 2.8 nm, respectively. Carbohydrates and proteins of the UP extract may participate in the synthesis and capping of the nanoparticles. The UP extract, Ag@UP, and Au@UP were assessed for their antimicrobial activity against Escherichia coli, Staphylococcus aureus, Pseudomonas aeruginosa, Candida albicans, and Candida auris. Ag@UP showed the highest antimicrobial activity with very low MIC and MBC values for all the tested bacteria, and Au@UP demonstrated to be very effective against biofilm-producing bacteria. The antifungal properties of both Ag@UP and Au@UP were remarkable, inhibiting hyphae formation. This study points towards a very promising biomedical exploitation of this invasive brown algae.